Comparison of the offensive and defensive level between goals of an adult female futsal championship - Miranda, Bruno Luiz Galvão de (2022)
Introduction: The offensive and defensive level of goalkeepers within futsal has grown exponentially, due to changes in the rules of the sport, making this position vital for movements and victories during matches. Objective: The objective of the present study was to quantify and compare the offensive and defensive level between goalkeepers of classified and disqualified teams from the first phase of a state championship. Materials and Methods: It was composed of 29 matches of the Open Cup of Futsal Women Adult 2017 in São Luís-MA with eight teams (divided and two groups). The recordings took place with a video camera in a reserved place near the court. Six game actions (offensive and defensive) were analyzed. For statistics, the shapiro-wilk and anova tests were used with post-hoc tuckey and bonferroni tests using the Bioestat 5.3 software. Results: It identified a greater use of offensive actions between groups, ranked players performed more offensive and defensive actions, the pass with the feet and pitches with the hands stood out between the two groups, no significant differences were identified in any action between the groups. Conclusions: Therefore, the goalkeepers of the classified teams contributed more frequently in the offensive and defensive movements during the games. Although there were no statistically significant differences between classified and declassified.